Identifying the intervention mechanisms of polydatin in hyperuricemia model rats by using UHPLC-Q-Exactive Orbitrap mass spectroscopy metabonomic approach - Ge, Xueli; Su, Zhenguo; Wang, Yuhao; Zhao, Xue; Hou, Kaifei; Zheng, Shuna; Zeng, Pengjiao; Shi, Zhongqi; Hu, Senhao; Wang, Yuqing; Zhou, Mengchen; Zhang, Jiayu; et al. (Frontiers in Nutrition, 2023)
Polydatin is a functional compound derived from mulberry, grape and polygonum cuspidatum, showing good lower uric acid effects. However, the urate-lowing effects and potential molecular mechanism still need further study. In this study, a hyperuricemic rat model was set up to assess the lower uric acid effects of polydatin. Body weight, serum biochemical indicators and histopathological parameters of rats were evaluated. UHPLC-Q-Exactive Orbitrap mass spectrometry based-metabolomics approach was applied to explore the potential action mechanisms after polydatin treatment. The results showed a recovery trend in biochemical indicators after polydatin administration and polydatin could alleviate the damages of liver and renal. Obvious alterations were observed in hyperuricemic rats compared with control group via untargeted metabolomics analysis. Fourteen potential biomarkers in model group were identified through principal components analysis (PCA) and orthogonal partial least squares-discriminant analysis (OPLS-DA). These differential metabolites were involved in amino acid metabolism, lipid metabolism and energy metabolism. Of all metabolites, the levels of L-phenylalanine, L-leucine, O-butanoylcarnitine, dihydroxyacetone phosphate decreased and the levels of L-tyrosine, sphinganine and phytosphingosine increased significantly in hyperuricemic rats. After administration of polydatin, the fourteen differential metabolites could be inverted varying degrees via regulating the perturbed metabolic pathway. The findings demonstrate polydatin is a promising potential adjuvant in lower uric acid aspects and alleviate hyperuricemia-related diseases.